Mapping Active Lava Flows from the 2022 Mauna Loa Eruption Using NOAA-20 and S-NPP Satellite Data - Ramayanti, Suci; Lee, Chang-Wook; Iryanti, Mimin; Indrasari, Widyaningrum; Hamidah, Ida; Hasanah, Lilik (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
The development of satellite data has played an important role in monitoring natural disasters on the Earth's surface. Providing an overview of the current conditions of a volcanic crisis, including information on lava flow extension, is a challenge in observing volcanoes. Various methods were used to map lava flows, such as identifying lava on optical satellite images and detecting thermal anomalies emitted by hot lava. This study aimed to generate a preliminary map of active lava flow caused by the 2022 Mauna Loa eruption in near real-time by analyzing fire radiative power (FRP) data acquired from Suomi National Polar-orbiting Partnership (S-NPP) and National Oceanic and Atmospheric Administration-20 (NOAA-20) satellites. FRP data was filtered to identify lava flow using statistically determined thresholds from its value distribution, including the 5th percentile, 3rd quartile, mean, and 95th percentile. The obtained active lava flow map is evaluated using confusion matrix analysis by comparing the estimated map with the reference map. The maps generated using various thresholds were compared, and the best result was provided by the threshold of the 3rd quartile, with S-NPP and NOAA-20 FRP threshold values of 27.2 and 27.9 MW/pixel, respectively, with overall accuracy reaching 97%. The higher threshold reduced the overestimated lava location represented by a false positive (FP) value. The results show that the active lava originated from the summit caldera, and the eruptive fissure on the northeast flank extended to the northeastern area with an estimated daily distance reaching about 18 km from a certain reference point. This preliminary lava flow map can provide general information regarding areas prone to lava flows, especially around Mauna Loa, and support related parties in updating hazard zones rapidly. The findings should help make immediate decisions for evacuation routes and public warnings when an eruption occurs without visiting the volcanic area directly.